GOVERNANCE QUALITY, ECONOMIC SUSTAINABILITY, AND TAX REVENUE: A MODERATION ANALYSIS - Kalsum, Umi; Susetyo, Didik; Saftiana, Yulia; Fuadah, Luk Luk (LPPM Universitas Jambi, 2026)
This study examines the effect of governance quality on tax revenue and investigates the moderating role of economic sustainability. Grounded in the Quality of Governance (QoG) framework, Agency Theory, and Sustainable Growth Theory, this research explains how institutional quality influences fiscal capacity and how economic sustainability conditions this relationship. The study employs an explanatory quantitative design using an unbalanced panel dataset of seven ASEAN countries over the period 1996–2023, comprising 196 observations selected through purposive sampling based on data availability and consistency. Secondary data are obtained from the World Bank’s Worldwide Governance Indicators (WGI), World Development Indicators (WDI), and the International Country Risk Guide (ICRG). The analysis is conducted using panel data regression and Moderated Regression Analysis (MRA) with robust standard errors to address heteroskedasticity and autocorrelation. The results show that government effectiveness, regulatory quality, rule of law, and voice and accountability have positive and significant effects on tax revenue, while control of corruption and political stability exhibit negative short-term effects. Furthermore, economic sustainability strengthens the positive relationship between governance quality and tax revenue while weakening the effects of certain governance dimensions. These findings indicate that governance reforms alone are insufficient without supportive and sustainable economic conditions. This study contributes by integrating governance quality and economic sustainability into a unified framework and provides policy implications for developing countries in designing integrated strategies to enhance tax revenue performance.